Las prácticas funerarias de los inicios de la Edad del Bronce en los páramos del noroeste de Burgos (España): El túmulo posdolménico de Arroyo de las Vegas en Sargentes de la Lora - Rodrigo Villalobos García; Angélica Santa Cruz del Barrio; Germán Delibes de Castro; Miguel Á. Moreno Gallo; Javier Basconcillos Arce; Xavier Bayer Rodríguez; Sandra Pastor Paredes; Teresa Fernández-Crespo; Olatz Villanueva Zubizarreta; Carlos P. Odriozola; Ana María Casas-Ferreira; Miguel del Nogal-Sánchez; et al. (Munibe Antropologia-Arkeologia)
Se presentan los resultados de la excavación y estudio de materiales del túmulo de Arroyo de las Vegas. Este es un yacimiento funerario que viene a rellenar el vacío documental referente al monumentalismo funerario de comienzos del II milenio cal a.C. de la zona central del norte peninsular. Arquitectónicamente estaba compuesto por una pequeña cámara enlosada en el centro de un túmulo rodeado por un peculiar anillo de lajas. Sus artefactos, en su mayoría cerámicas a mano, permiten encuadrarlo en el Bronce Antiguo. Los restos humanos de, al menos, 3 adultos, 1 infantil y 1 posible perinatal fueron depositados en la cámara a lo largo de distintos momentos del Bronce Antiguo según el estudio de las dataciones radiocarbónicas. Los análisis de isótopos estables de estos individuos revelan una dieta mixta muy homogénea y una escasa movilidad. Por todo ello interpretamos que esta fue la tumba de un pequeño grupo, quizás con lazos familiares, de marcado carácter localista. ABSTRACT: Arroyo de las Vegas is a mound located in the northern Burgos province, the central part of the mountainous region of Northern Spain. It was completely excavated in 2017-2019 and this, together with the archaeological, anthropological and archaeometric study of the materials, help to shed new light on the monumental funerary practices of the early 2nd millennium cal BCE of this area. The monument hosted a small oval chamber (2 meters of diameter) constructed by medium size rocks with its ground paved with slabs. Around the chamber a mound of rocks was also constructed, with a peripheral “ring of slabs” (8 meters of diameter). All the prehistoric artefacts recovered, mainly hand-made pottery with decorations such as stamped fingertips («digitaciones»), clay cords («cordones») or «barbotina» surfaces, but also a flint arrowhead and non-exotic beads, point to an Early Bronze Age chronology. Other modern materials such as a wheel thrown small pot suggest some kind of activity during the Middle Age, probably a looting event of the prehistoric tomb. At least 3 adults, 1 infant and 1 perinatal were deposited in the chamber, and according to the taphonomic analysis they probably formed part of a primary burial. The analysis of the radiocarbon dates prove that they were buried along different phases of the Early Bronze Age (2200-1500 cal BCE). Finally, stable isotope analyses suggest a homogeneous mixed diet and no evidence of mobility. We compare this data with the former evidence from the Neolithic and Copper Age burial practices of la Lora and found that the Early Bronze Age people of Arroyo de las Vegas constructed a tomb for a small group, perhaps linked by kin ties, whose ways of life and culture were probably not related to long distance networks, as happened during the 4rd-3rd millennia cal BCE, but rather local.